Streptococcus Gallolyticus Subsp. Pasteurianus Infection In A Neonatal Intensive Care Unit. Issue 11 (November 2016) - Saegeman, Veroniek; Cossey, Veerle; Loens, Katherine; Schuermans, Annette; Glaser, Philippe
Abstract : We report nosocomial transmission of Streptococcus gallolyticus subsp. pasteurianus among 3 neonates, 1 of whom died. Genome analysis of the strains showed a specific pattern of metabolic and regulatory functions as well as of expressed antigens and antibiotic resistance genes that might have contributed to their specific virulence.